2023
DOI: 10.1007/s13399-023-04311-9
|View full text |Cite
|
Sign up to set email alerts
|

Experimental demonstration of 80 kWth chemical looping combustion of biogenic feedstock coupled with direct CO2 utilization by exhaust gas methanation

Abstract: Chemical looping combustion is a highly efficient CO2 separation technology without direct contact between combustion air and fuel. A metal oxide is used as an oxygen carrier in dual fluidized beds to generate clean CO2. The use of biomass is the focus of current research because of the possibility of negative CO2 emissions and the utilization of biogenic carbon. The most commonly proposed OC are natural ores and residues, but complete combustion has not yet been achieved. In this work, the direct utilization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…Kermani and Houshfar [45] analyzed the energetic and exergetic performance of a biomass (wood chips and wheat straw chopped wood) combustion plant integrated with post-combustion CO 2 separation via absorption and subsequent methanation. Recently, Fleiß et al [46] successfully demonstrated the operation of an 80 kW th CLC unit fed by bark mulch with direct utilization of the flue gas stream in a fluidized bed methanator and performed a scale-up study to a 100 MW th plant. Finally, Brachi et al [9] investigated the performance of an integrated CLC-methanation plant relying on solar torrefied agro-industrial biomasses as input fuel through model computations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kermani and Houshfar [45] analyzed the energetic and exergetic performance of a biomass (wood chips and wheat straw chopped wood) combustion plant integrated with post-combustion CO 2 separation via absorption and subsequent methanation. Recently, Fleiß et al [46] successfully demonstrated the operation of an 80 kW th CLC unit fed by bark mulch with direct utilization of the flue gas stream in a fluidized bed methanator and performed a scale-up study to a 100 MW th plant. Finally, Brachi et al [9] investigated the performance of an integrated CLC-methanation plant relying on solar torrefied agro-industrial biomasses as input fuel through model computations.…”
Section: Introductionmentioning
confidence: 99%
“…BECCU with CO 2 conversion into renewable fuels is thus gaining significant attention to increase the penetration of renewable energies, reduce greenhouse gas emissions, and convert H 2 into more easily exploitable fuels [9,[43][44][45][46]. This study aims to contribute to the existing literature on the topic by estimating key energetic and economic performances of an integrated process targeting both BECCU and methane production.…”
Section: Introductionmentioning
confidence: 99%